ORGANIZATIONAL EFFECTIVENESS OF THE PROCUREMENT SERVICE SECTION OF SOUTH OF TANGERANG CITY - Arie Kurniawan; Retnowati Tuti; Ma’mun Murod; Evi Satispi; Djoni Gunanto (POLITICO, 2021)
Procurement of goods and services that are in government with limited resources and regulations that change according to the times of course these change will affect organizational effectiveness. In such an environment the procurement of goods and services must be responsive and clever in anticipating to maintain their existence and function. For an organization to maintain its existence and function, it must be effective to support this the South Tangerang City Procurement Service Section has an important contribution in the implementation of the goods or services procurement process. Based on these conditions a research was conducted with the title: "Organizational Effectiveness of The Procurement Services Section of South Tangerang City". The theory used in this study from Richard M. Steers (1985: 206), the capability of adaptability, productivity, and job satisfaction. The method used in this research is descriptive research with a qualitative approach. This research uses the determination or selection of informants by using Purposive methods. Data sources were obtained from interviews, documentation, and observations with the validity of the data used in this research were Triangulation techniques. The result of this research explained that the effectiveness of the Procurement Service Section of South Tangerang City in adaptability is optimal, productivity is optimal, and job satisfaction is good, overall it is effective to do the jobs and the functions. Supporting factor are training and coaching employees, satisfaction in work and smooth communication while inhibiting factor is the lack of quality of Human Resources and the low quality of supporting facilities in the procurement service section of South Tangerang City.